Evaluation of the Safety Performance of Turbo Roundabouts by Means of a Potential Accident Rate Mode - Raffaele Mauro; Marco Cattani; Marco Guerrieri (The Baltic Journal of Road and Bridge Engineering, 2015)
Turbo roundabouts are a particular road intersection layout, designed to increase the safety of double-lane roundabouts, while maintaining their excellent capacity. The main feature of this new concept of roundabout is the impossibility to move from one lane to another, provided by physical barriers marking the lanes. The paper shows an application to turbo roundabouts of a potential accident rate model, aiming to evaluate their safety improvement. The model is based on the concept of potential conflict: each vehicle involved in a general intersection performs a series of maneuvers which potentially imply a crash, according to the actual traffic. The number of accidents related to each critical maneuver is proportional to the number of times this maneuver occurs at the intersection. In order to define the critical maneuvers, and hence the relevant potential conflicts, specific crash typologies for roundabouts are adopted. Traffic volumes are required, to evaluate the expected number of accidents, and also probabilities of accident for every critical maneuver. These ratios were obtained by a model calibration, based on actual accident and traffic data recorded on conventional single and double-lane roundabouts. The model was then used to compare four-leg turbo roundabouts to conventional roundabouts. The comparisons have taken into account only basic differences in layout, such as geometric elements, that also play a role in determining safety performances of a roundabout. The results obtained show that turbo roundabouts significantly decrease the accident rate with respect to conventional roundabouts, by eliminating conflicts between circulating and exiting vehicles.